Indoor air quality and prevalence of sick building syndrome among university laboratory workers - Md Saad, Zuliza; Rasdi, Irniza; Zainal Abidin, Emilia (Global Society of Scientific Research and Researchers, 2016)
This study was carried out to investigate the association between indoor air quality (IAQ) and prevalence of sick building syndrome (SBS) among laboratory workers. A cross-sectional comparative study was conducted among 264 laboratory workers in a private university (88% response rate). A self-administrated questionnaire was used to determine the prevalence of SBS. Temperature, air movement, relative humidity (RH), concentration of carbon monoxide, (CO) carbon dioxide (CO2) and total volatile organic compounds (TVOCs) were measured objectively in 55 laboratories. The average temperature of dry laboratories was significantly higher (M=25.110C) than wet laboratories (M=23.770C). The mean of CO in wet laboratories (M=1.15ppm) was significantly higher than in dry laboratories (M=0.89ppm), (p<0.002). The prevalence of SBS among respondents at wet laboratories was significantly higher (45.4%) compared to dry laboratories (20%), (?2 = 19.5). The most prevalent reported symptoms were drowsiness (18.5%), followed by irritated stuffy runny nose (13.4%), headache (10.9%), and skin rashes or itchiness (10.1%). At dry laboratories, higher temperature was found to be significantly associated with SBS among workers (?2=-0.38, p =0.042). Low temperature and higher CO at wet laboratories were found to be significantly associated with SBS (?2 =-0.33, p =0.021) and (?2 =-0.24, p =0.044). In summary, this study revealed that poor IAQ affects the SBS among workers at both laboratories. Thus, further assessment and remedial action are warranted to reduce the SBS symptoms among laboratory workers.